Implementing video visits into an orthopedic hip arthroscopy practice: a case study. Issue 4 (18th May 2021) - Wickman, John; Ferlotti, Colleen; Ferrell, Justin; Hutyra, Carolyn; Phinney, Donna; Wahl, Megan; Mather, Richard C
Abstract: Telehealth videoconferencing has been shown to be feasible, cost-effective and safe in numerous fields of medicine. In an effort to increase access and improve the quality of care offered to patients we implemented a telehealth initiative allowing for remote orthopedic clinic visits at a major academic medical center. Here we report on our experience and early outcomes. A telehealth platform was launched for a single fellowship trained orthopedic surgeon at a major academic hospital in August 2018. New patients residing outside the metro area, all return patients and patients with an uncomplicated post-operative course were offered the option to complete patient encounters remotely via a telehealth platform. Each patient was offered a Patient Satisfaction Survey following video visit. Patient zip codes were used to estimate patient commutes. Ninety-six percent of patients agreed/strongly agreed with the statement 'I was satisfied with my Telehealth experience' while 51% agreed/strongly agreed with the statement 'This visit was just as good as a face to face visit'. In all, 94% of patients agreed/strongly agreed with the statement 'Having a telehealth visit made receiving care more accessible for me'. The median miles saved on commutes were 123.3 miles. The no show rate for telehealth visits was 8.2% versus 3.2% for in-person ( P  < 0.001). Telehealth video visits provided patients with a modality for completing orthopedic clinic visits while maintaining a high-quality care and patient satisfaction. Patient convenience was optimized with video visits with elimination of long commutes. Level of evidence: IV.